2010
DOI: 10.1007/dcr.0b013e3181e751df
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology Predictors of Medically Refractory Ulcerative Colitis

Abstract: Medically refractory ulcerative colitis was associated with initial biopsy findings of severe cryptitis, lymphoid follicles, and erosions. Refractory disease was not predicted by the severity or extent of endoscopic findings. In younger patients, the presence of lymphoid follicles, and in older patients, severe cryptitis, were the most important predictors of medically refractory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…1,3 We hypothesized that in adults and children UC course depends upon initial disease phenotype, therapy offered, and intrinsic patient biology. Initial disease severity, lack of response to early therapy, hypoalbuminemia, anemia, low serum 25 (OH) D, colonic histology, and specific genetic polymorphisms have been associated with worse clinical outcomes 2,[4][5][6] , though data largely come from studies lacking standardised treatment and many have focused on acutely ill hospitalized patients. In a paediatric observational registry with no standardisation of initial therapy, less than 40% of children newly diagnosed with UC were in CS-free remission without the need for immunomodulators or anti-TNFα therapy one year after diagnosis 7 .…”
Section: Introductionmentioning
confidence: 99%
“…1,3 We hypothesized that in adults and children UC course depends upon initial disease phenotype, therapy offered, and intrinsic patient biology. Initial disease severity, lack of response to early therapy, hypoalbuminemia, anemia, low serum 25 (OH) D, colonic histology, and specific genetic polymorphisms have been associated with worse clinical outcomes 2,[4][5][6] , though data largely come from studies lacking standardised treatment and many have focused on acutely ill hospitalized patients. In a paediatric observational registry with no standardisation of initial therapy, less than 40% of children newly diagnosed with UC were in CS-free remission without the need for immunomodulators or anti-TNFα therapy one year after diagnosis 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have evaluated histological findings as predictors of medically refractory disease. Melson et al [33] showed that medically refractory UC is not predicted by the severity or extent of endoscopic findings but is associated with histological findings such as severe cryptitis and lymphoid follicles. The presence of rectal sparing may indicate more aggressive disease and is less responsive to medical treatment among pediatric patients with UC [34].…”
Section: Discussionmentioning
confidence: 99%
“…They are, both, identified in active phase of UC [2]. They are predictive for an aggressive, refractory disease especially in older patients [19]. One study identified cryptitis in the majority of relapsing patients, while none of the non-relapsers had this feature on the initial biopsy [18].…”
Section: Cryptitis and Crypt Abscessesmentioning
confidence: 99%